An integrative multilevel review of thriving at work: Assessing progress and promise. (25th October 2021) - Goh, Zen; Eva, Nathan; Kiazad, Kohyar; Jack, Gavin A.; De Cieri, Helen; Spreitzer, Gretchen M.
Summary: Thriving at work is a notable construct given its role in individual health and developmental outcomes. According to the Socially Embedded Model of Thriving (SEMT), individuals thrive at work when embedded in environments that support agentic behaviors and can self‐sustain this state through positive spirals of agentic behaviors, resources, and thriving. The SEMT is inherently multilevel, yet there are two unarticulated but critical multilevel issues in existing scholarship: a paucity of research reflecting these multilevel features of the SEMT and an incipient multilevel conceptualization of thriving that has little theoretical justification. As a catalyst for progress, we present an integrative review drawing from the SEMT and other supplementary theoretical perspectives to define a multilevel conceptualization of thriving at work. Through this lens, we organize, synthesize, and evaluate the body of evidence, integrating the multilevel view of thriving within established scholarship. To substantiate our framework theoretically, we articulate how lower level processes unfold to develop higher level collective manifestations of thriving at work. We identify opportunities for theoretical and empirical advancement, coupled with specific, actionable recommendations, to deepen a multilevel conceptualization of thriving. Altogether, we advance thriving at work as a multilevel construct meaningful at three levels—individuals, dyads, and collectives.